Efficacy of hepatitis B vaccination in patients with ulcerative colitis: a prospective cohort study - Anurag Mishra; Amarender Singh Puri; Sanjeev Sachdeva; Ashok Dalal (Intestinal Research, 2022)
Background/Aims Response to vaccine in patients with inflammatory bowel disease is lower than in the general population. We aimed to evaluate the efficacy of hepatitis B virus (HBV) vaccination in patients with ulcerative colitis (UC) versus controls. Methods We prospectively compared antibody response to HBV vaccination in 100 patients with UC versus controls. HBV vaccination was given to all the cases and controls at 0, 1 and 6 months. Anti-hepatitis B surface (anti-HBs) titers were then measured 4 weeks after the first and the third dose. Adequate immune response (AIR) was considered if the anti-HBs titer was >10 IU/L and effective immune response (EIR) if the anti-HBs titer was >100 IU/L. Results Median anti-HBs titer was lower in patients with UC than controls (67 IU/L vs. 105 IU/L, P<0.01). AIR and EIR were significantly lower in patients than in controls (82% vs. 96%, P=0.001; 41% vs. 66%, P<0.001, respectively). Univariate analysis showed that age <30 years, mild to moderate severity of disease, disease duration <5 years, male sex, post first dose anti-HBs titer >2 IU/L and non-exposure to corticosteroids, azathioprine and biologicals were predictors of AIR in patients with UC (P<0.05). Multivariate analysis revealed that only non-exposure to corticosteroids, azathioprine and biologicals, male sex, and disease duration <5 years were independent predictors of AIR. Conclusions Response rate to the HBV vaccination in patients with UC was significantly lower as compared to the controls. Male sex, shorter disease duration, and non-exposure to immunomodulators were independent predictors of AIR.